Cervical surveillance in HIV-positive women: a genitourinary medicine clinic experience. Issue 2 (1st April 2009) - Ibrahim, Fatima W; Schembri, Gabriel; Dhar, Jyoti; Taha, Huda; Ariyanayagam, Sati
Abstract : Background: The prevalence of cervical intraepithelial neoplasia (CIN) is increased in HIV infection. The UK National Health Service Cervical Screening Programme (NHSCSP) guidelines therefore provide specific recommendations for HIV-positive women. An audit of cervical surveillance in HIV-positive women who attend the genitourinary medicine (GUM) department at the Leicester Royal Infirmary, Leicester, UK was conducted. The objectives were to assess adherence to UK and local screening guidelines, prevalence of cervical pathology and appropriate referral for colposcopy. Methods: A retrospective case note review of 130 HIV-infected women attending the GUM department between January 2000 and December 2005 was undertaken. Results: Results showed that 76.2% of patients had cervical cytology within a year of HIV diagnosis and 42.4% of patients had abnormal cytology. All patients with dyskaryosis were referred for colposcopy according to local and national guidelines. Cytology results were consistent with histological findings and the prevalence of CIN was 15.2%. CD4 counts at presentation were significantly lower in those with dyskaryosis compared with those without dyskaryosis ( p = 0.038). Twenty-two patients were lost to follow-up after initial cytology. Discussion and conclusions: A designated health advisor in the GUM department co-ordinates cervical surveillance in HIV-positive women. This, together with an increasingly integrated service with family planning services, may contribute to relatively successful surveillance. Overall, patients are carefully monitored to ensure that surveillance is adequate. Extra vigilance is, however, required and further cost-effective measures in future may include more active involvement of general practitioners.